2014
DOI: 10.1016/j.envres.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Peak expiratory flow, breath rate and blood pressure in adults with changes in particulate matter air pollution during the Beijing Olympics: A panel study

Abstract: Objectives This study aims to examine whether changes in short-term exposures to particulate matter are associated with changes in lung function, breath rate, and blood pressure among healthy adults and whether smoking status modifies the association. Methods We took advantage of the artificially controlled changes in air pollution levels that occurred during the 2008 Olympic Games in Beijing, China and conducted a panel study of 201 Beijing residents. Data were collected before, during, and after the Olympi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 49 publications
(52 reference statements)
6
37
0
6
Order By: Relevance
“…These findings are in agreement with the epidemiological evidence that air pollution attenuates lung function in children (Gauderman et al, 2007;Urman et al, 2014). In contrast, AM carbon was not associated with pulmonary function parameters in a study of adults (Nwokoro et al, 2012), which is contrary to the respiratory effects of air pollution provided by epidemiological studies (Eckel et al, 2012;Forbes et al, 2009;Mu et al, 2014). The reason of the inconsistent relationship between AM carbon and lung function in adults is, however, unknown.…”
Section: Studysupporting
confidence: 78%
“…These findings are in agreement with the epidemiological evidence that air pollution attenuates lung function in children (Gauderman et al, 2007;Urman et al, 2014). In contrast, AM carbon was not associated with pulmonary function parameters in a study of adults (Nwokoro et al, 2012), which is contrary to the respiratory effects of air pollution provided by epidemiological studies (Eckel et al, 2012;Forbes et al, 2009;Mu et al, 2014). The reason of the inconsistent relationship between AM carbon and lung function in adults is, however, unknown.…”
Section: Studysupporting
confidence: 78%
“…Our results showed that the breath flow and volume parameters decreased in animals after exposure to aPM 2.5 2327, supporting the hypothesis that PM 2.5 exposure might reduce lung function. As other traditional parameters, such as P:F ratio or Sa0 2 , are important in evaluating lung function, these indications will be included in further investigation.…”
Section: Discussionsupporting
confidence: 86%
“…53 In a panel study of children living in Beijing, Lin et al (2011) reported reductions in both air pollutant concentrations and exhaled nitric oxide levels during the Olympic Games compared to the Pre-Olympic period, with each 4.0 μg/m 3 increase in black carbon associated and 149 μg/m 3 increase in PM 2.5 concentration associated with 16.6% (95% CI = 14.1%, 19.2%) and 18.7% (95% CI = 15.0, 22.5%) reductions in eNO, respectively. 54 Further, they reported similar reductions in markers of oxidative stress during the Olympic Games (8-oxodG: −37%, 95% CI = −54%, −16%; urinary malonaldehyde: −25%, 95% CI = −34%, −15%) and similarly, decreased 9-oxodG and malonaldehyde levels associated with increased pollutant concentrations (black carbon, PM 2.5 , SO 2 , NO 2 , and CO).…”
Section: Air Pollution Reductions and Large Sporting Eventsmentioning
confidence: 99%
“…They have examined health responses to air quality actions directed at traffic pollution, 33,37,42,43 industrial emissions, 11-15,17,29 home heating fuel, 18,22 and both long term reductions in the entire air pollution mixture, 30 and short term temporary reductions ranging from 14 to 47 days. 44,50-52,54,55,59,60,62,64 They have assessed concentration changes and health responses to measured/estimated concentrations of TSP, 28,53 PM 10 , 11-15,38,53,64 PM 2.5 , 30,44,46,51,53,54,59 black carbon, 54 black smoke, 18,21,22 sulfate, 33,44,46,51 other PM size fractions, 44,46,51,53,57 PM components and ions, 44,46,51 NO 2 or NO x , 30,44,46,51,59,60,64 SO 2 , 18,21,22,28,29,33,44,46,51,60,64 CO, 44,46,51,59,60 and O 3 . 42-44,46,51,59 Further, some of these air pollutant concentration changes have been large (e.g.…”
Section: Conclusion and Lessons Learnedmentioning
confidence: 99%
See 1 more Smart Citation